ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI USIA KAWIN PERTAMA DAN FERTILITAS DI KECAMATAN NEGARA KABUPATEN JEMBARANA - Prayogi, I Wayan Agus; Sudibia, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022DO - 10.24843/EEB.2022.v11.i09.p01, 2022)
This study aims to analyze 1) the effect of women's education, employment status, socio-economic conditions of parents and culture on the age of first marriage in the State District of Jembarana Regency; 2) the influence of women's education, employment status, parents' socio-economic conditions and culture on fertility in the State District of Jembrana Regency; 3) women's education, employment status, parents' socio-economic conditions and culture indirectly affect fertility through age at first marriage in the Negara District, Jembrana Regency. The data analysis technique used is descriptive statistics and inferential statistics consisting of path analysis and Sobel test. The results showed that women's education, parents' socioeconomic conditions, and employment status had a positive direction and partially significant effect on the age at first marriage of women of childbearing age (PUS) in Negara District, Jembrana Regency. Culture has a negative direction and partially significant effect on the age at first marriage of women of childbearing age (PUS) in Negara District, Jembrana Regency. Women's education and employment status have a negative direction and partially significant effect on the fertility of women of childbearing age (PUS) in Negara District, Jembrana Regency. Culture has a positive direction and partially significant effect on female EFA fertility in Negara District, Jembrana Regency. Age at first marriage (Y1) has a negative direction and partially significant effect on fertility (Y2) female EFA in Kecamatan Negara, Kabupaten Jembrana. Based on the indirect effect test, the results show that women's education, parents' socioeconomic conditions, employment status, and culture indirectly affect fertility through the age of first marriage in women of childbearing age (PUS) in Negara District, Jembrana Regency.